Minimum temperature differences between the meteorological screen and grass in radiative frost nights - Vieira, Nilson Aparecido [UNESP]; Caramori, Paulo Henrique; De Aguiar E Silva, Marcelo Augusto; Nitsche, Pablo Ricardo (Universidade Estadual de Londrina, 2018)
A phenomenon called thermal inversion, in which there is the accumulation of colder and denser air in the layers closer to the soil, occurs in radiative frost nights, resulting in a temperature gradient with differences between the meteorological screen and grass, which vary depending on cooling conditions. Knowing this temperature difference assists in taking preventive measures against radiative frosts, as well as in estimating the probability of their occurrences. In this context, this study aimed to verify the adjustment of different probability distributions to determine the differences between the minimum temperature measured in the meteorological screen and grass temperature below 0 °C for eight regions of the Paraná State, as well as the probability of occurring these differences and adjust estimation equations of grass temperature from minimum air temperature. Temperature differences between the screen and grass were calculated and probability distributions of their occurrences were adjusted in order to determine risks per intervals of temperature differences. Estimation equations of grass temperature were adjusted from minimum screen temperatures. Average gradients of minimum temperature were observed between the screen and grass ranging from 4.2 to 6.3 °C in the analyzed regions. The average temperature difference measured in the meteorological screen and grass for the Paraná State was 5 °C. The probabilistic model of normal distribution is the most suitable for determining the probability of occurring the differences between the screen and grass temperatures for the Paraná State. Regional relief and climate conditions influence the magnitude of the minimum temperature gradient measured in the meteorological screen and grass. Estimation equations can be useful to determine the grass temperature based on the minimum air temperature for periods in which there is no such data and thus provide a subsidy for studies of risk analysis of frosts. The results of this analysis are empirical and the equations should be used in regions in which they were adjusted aiming at a higher accuracy.
Diferenças de temperatura mínima entre o abrigo meteorológico e a relva em noites com geadas
Keywords: Frost risk; Grass temperature; Temperature gradient; Thermal inversion